2021
DOI: 10.1037/ccp0000690
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal cognitions as a mechanism of change in cognitive behavioral therapy for generalized anxiety disorder? A multilevel dynamic structural equation model approach.

Abstract: Objective: This study aimed to investigate the effects of changes in interpersonal cognitions on outcome during cognitive behavioral therapy (CBT) for generalized anxiety disorder (GAD) and how these effects are moderated by patients' interpersonal problems at intake. Method: A sample of 80 adult patients diagnosed with GAD who were undergoing CBT within a randomized controlled trial completed a questionnaire concerning interpersonal problems at baseline as well as measures of changes in interpersonal and self… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The current narrative review also found that interpretation bias was not a significant mediator of the relationship between increased trait mindfulness and reductions in anxiety symptoms following MBSR (Hoge et al, 2020 ). Moreover, changes in negative cognitions appear to be particularly relevant mechanisms of anxiety reduction following CBT (e.g., Gallagher et al, 2020 ; Gómez Penedo et al, 2021 ; Kladnistki et al, 2022 ). The current findings may support the possibility that, in GAD, mindfulness exerts its effects through practice of adopting a mindful, non-judgemental, and distanced relationship with one’s thoughts and feelings, rather than challenging maladaptive thinking, as in other Cognitive Therapy approaches (Baer, 2003 ; Kabat-Zinn, 2003 ; Wells, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current narrative review also found that interpretation bias was not a significant mediator of the relationship between increased trait mindfulness and reductions in anxiety symptoms following MBSR (Hoge et al, 2020 ). Moreover, changes in negative cognitions appear to be particularly relevant mechanisms of anxiety reduction following CBT (e.g., Gallagher et al, 2020 ; Gómez Penedo et al, 2021 ; Kladnistki et al, 2022 ). The current findings may support the possibility that, in GAD, mindfulness exerts its effects through practice of adopting a mindful, non-judgemental, and distanced relationship with one’s thoughts and feelings, rather than challenging maladaptive thinking, as in other Cognitive Therapy approaches (Baer, 2003 ; Kabat-Zinn, 2003 ; Wells, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…In future work, inclusion of ‘stand-alone’ interventions and evidence-based treatment controls (i.e., CBT) would help to delineate the distinct therapeutic mechanisms of mindfulness-based programs. CBT-based cognitive techniques may be integral in targeting key maladaptive cognitive biases involved in GAD and worry symptoms (Dugas et al, 2007 ; Gómez Penedo et al, 2021 ; Kladnistki et al, 2022 ). However, specific mindfulness techniques may hold promise as treatment adjuncts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to estimate the processes effects on outcome, we followed recent literature that applied DSEM, computing separate models for each process (Gómez Penedo, Schwartz, et al, 2022; Gómez Penedo et al, 2021; Rubel et al, 2019). In these models, at the within-patient level, variations in outcome in a given session are predicted by outcome variations in the previous session (i.e., autoregressive effects) and process variations in the previous session (i.e., cross-lagged effects).…”
Section: Methodsmentioning
confidence: 99%
“…All participants signed a written informed consent form. Full methods of the study were documented at the Open Science Framework (OSF; https://osf.io/mv7kd; Go ´mez Penedo, Meglio, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…2011). Furthermore, a recent meta‐analysis found interpersonal problems to be significantly related to worse treatment outcomes across depressive and anxiety disorders (Gómez Penedo and Flückiger 2023). This underlines the need for further treatment development in relation to interpersonal problems with an aim to increase and broaden treatment effects.…”
Section: Introductionmentioning
confidence: 99%